AGILE METHODOLOGIES IN SOFTWARE MAINTENANCE:A SYSTEMATIC REVIEW (Informatica, 2016)
Agile Methodologies has been gaining popularity since 2000. The Software Maintenance phase of software lifecycle is the most expensive and tedious in nature and use of Agile methodologies helps in maintaining software over time in flexible and iterative manner. This study reviews several papers with different case studies to evaluate the performance and quality of software using agile methodologies. In this study, more than 30 research studies are investigated which are conducted between 2001 and 2015 and have been categorized according to the publication year, datasets, tools, type of techniques etc. This will be the first review paper on the use of the Agile in software maintenance which will help the researchers and encourages companies and beginners to adopt these methodologies to gain software quality. This study would also be helpful to professional academicians to identify the current trends and future gaps in the field of agile methodologies.